1996
DOI: 10.1103/physrevlett.76.1433
|View full text |Cite
|
Sign up to set email alerts
|

Self-Energy Correction to the Hyperfine Structure Splitting of Hydrogenlike Atoms

Abstract: A first testing ground for QED in the combined presence of a strong Coulomb field and a strong magnetic field is provided by the precise measurement of the hyperfine structure splitting of hydrogenlike 209 Bi. We present a complete calculation of the one-loop self-energy correction to the first-order hyperfine interaction for various nuclear charges. In the low-Z regime we almost perfectly agree with the Za expansion, but for medium and high Z there is a substantial deviation.PACS numbers: 31.30. Gs, 31.15.Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 29 publications
2
54
4
Order By: Relevance
“…In order to compare our calculations with the data we need ∆E QED . It was calculated in several papers and the results are consistent [11,[16][17][18][19]. In [19] it was shown that ∆E QED is insensitive to details of the magnetization distribution.…”
Section: Effects Of the Core Polarizationmentioning
confidence: 66%
See 3 more Smart Citations
“…In order to compare our calculations with the data we need ∆E QED . It was calculated in several papers and the results are consistent [11,[16][17][18][19]. In [19] it was shown that ∆E QED is insensitive to details of the magnetization distribution.…”
Section: Effects Of the Core Polarizationmentioning
confidence: 66%
“…The leading QED corrections originate from the one-loop self-energy and vacuum-polarization effects. The one-loop QED effects for hfs have been calculated by different groups and the results are consistent [11,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…(394) we would obtain in the nonrecoil limit ∆E(2P − 2S) = 0.0264 meV (257) instead of the result in eq. (255). Comparing these numbers we see that the numbers discussed in this Section may be used for estimates of the proton size contribution of order (Zα) 5 , but when the results of the Lamb shift measurements become available, this correction will require some kind of a self-consistent consideration.…”
Section: Nuclear Size and Structure Correctionsmentioning
confidence: 99%